Yield line analysis of reinforced concrete skew slab - Kumar, Rajesh; Mandal, S.; Kumar, Veerendra (Journal of Structural Engineering, 2024)
Reinforced concrete skew slabs with different boundary conditions have been analysed using yield line theory. The reinforcement is assumed orthogonal. The ratio of the span moments to support moments is kept equal to 0.75 and design tables are prepared. The results obtained are compared with the codal values (IS : 456-2000) for zero skew angle i.e. for rectangular slab and it is found that the results obtained are 0.75 times the codal values.